THE ISSUES OF TRANSLATION OF PHRASEOLOGICAL UNITS (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2024)
Deciphering a phraseological unit is certainly not a simple matter as it relies upon a few elements: different combinability of words, homonymy, synonymy, the polysemy of phraseological units, and the presence of erroneously indistinguishable units, which makes it important to consider the specific circumstance. Also, countless phraseological units have a complex expressive part in significance, which normally has a particular public element. The in advance of referred to decides the need to get to know the fundamental standards of the overall hypothesis of manner